Pengaruh Kepercayaan, Kemudahan Penggunaan dan Persepsi Risiko Terhadap Minat Beli Konsumen (Studi Pada Pengguna E-Commerce Sociolla di Kota Malang) - Kibiyana Cempaka Aditama Putri; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of trust, ease of use and risk perception on consumer buying interest (Study on Sociolla E-Commerce Users in Malang City). The type of research used is explanatory research with the method of distributing questionnaires. The sample in this study amounted to 100 respondents and data processing using SPSS computer program. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, statistical test and analysis of the coefficient of determination. The variables used in this study are the dependent variable buying interest, and the independent variables are trust, ease of use, and risk perception. The results of this study indicate that simultaneously there is a positive and significant influence. Partially, it is shown that the variables of Trust and Risk Perception have a positive and significant effect on the Purchase Interest variable, then the positive Ease of Use variable has no significant effect on the Consumer Buying Interest of Sociolla e-commerce users in Malang City. Keywords : Trust, Ease of Use, Risk Perception, Purchase Interest